The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1186/s12916-023-02748-3
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the cost-effectiveness of cervical screening in the context of routine HPV vaccination by optimizing screening strategies with respect to vaccine uptake: a modeling analysis

Abstract: Background Regarding primary and secondary cervical cancer prevention, the World Health Organization proposed the cervical cancer elimination strategy that requires countries to achieve 90% uptake of human papillomavirus (HPV) vaccines and 70% screening uptake. The optimal cervical screening strategy is likely different for unvaccinated and vaccinated cohorts upon national HPV immunization. However, health authorities typically only provide a one-size-fits-all recommendation for the general pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Our survey found that vaccinated women were more likely to have attended cervical screening and screened regularly than unvaccinated women. As illustrated in our recent cost-effectiveness study, the optimal screening strategies were likely different by vaccination coverage in the age cohort [ 30 ]. Among women who have received HPV vaccines, a longer screening interval following negative screening results would likely remain cost-effective on top of HPV vaccination in the vaccinated cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our survey found that vaccinated women were more likely to have attended cervical screening and screened regularly than unvaccinated women. As illustrated in our recent cost-effectiveness study, the optimal screening strategies were likely different by vaccination coverage in the age cohort [ 30 ]. Among women who have received HPV vaccines, a longer screening interval following negative screening results would likely remain cost-effective on top of HPV vaccination in the vaccinated cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal cervical screening strategy likely correlated with HPV vaccination uptake among screening females. Specifically, a longer screening interval may be preferred in cohorts with high HPV vaccine uptake [ 30 32 ]. Our findings provide information for policymakers to consider when updating switching screening recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer is the only cancer in the world that can be prevented by HPV vaccination [30 , 31] . Studies have shown that persistent infection with HR-HPV is the main cause of cervical cancer [32 , 33] .…”
Section: Discussionmentioning
confidence: 99%
“…Visual inspection with acetic acid may also be cost-effective in certain settings, such as rural areas. 91 Another study carried out in Sweden and Australia also showed that primary screening for HPV is better than both cytology-based methods and primary HPV screening followed by cytology. 92,93 A study conducted in Nicaragua also has found that HPV testing is a more cost-effective option than Pap testing.…”
Section: Screening Methods Of CC In Special Populationmentioning
confidence: 99%
“…[75][76][77][78] Age in years ACS (2012) USPSTF ( 2018 screening can be a cost-effective approach, but only if routine vaccination rates reach 75% or higher. 91 A systematic review of economic evaluations of CC screening methods showed that primary HPV DNA testing strategies are cost-effective in several settings.…”
Section: Screening Methods Of CC In Special Populationmentioning
confidence: 99%